Kičo apraiškos šiuolaikiniame interjere - Mačiulis, Algimantas (Journal of Architecture and Urbanism, 2008)
Manifestations of kitsch in Lithuanian modern interiorWith Lithuania’s regained statehood and introduction of free market conditions, the image of ours towns has improved. However, we can also observe some negative aspects: predominance of commercialism, manifestations of kitsch, particulary in interiors.Several kitsch manifestation trends can be distinguished in modern interior: (1) “Wild West”, reflections of the American cowboy cult and (2) primitive “national”, “country” style. Currently the trends of architecture stylized with folk art motives are flourishing, when using naturalistic, sham elements bad taste interiors are created that demonstrate a vulgar understanding of national traditions. Original interiors created in the 60s–80s are destroyed. Modern and stylish interiors in Vilnius, Kaunas, and other towns did not survive. Kitsch could be noticed in architecture of private dwelling houses as well, when buildings remind of castles, mills, elevators, etc. due to the use of unusual symbols.Manifestations of kitsch in the design of modern interior and urban architecture could be linked to post-modernism that propagates eclecticism, orientation to regionalism, “country” forms, retrospection to historism, “citing” in modern architecture historical and “local dialect” forms from a paradox to an ironic sarcasm.Santrauka. Peržvelgiamos kičo, stilizacijos, komerciškumo šiuolaikiniame interjere tendencijos. Išskiriamos kelios kičo apraiškos kryptys: 1) komercinis amerikietiškasis „laukinių Vakarų“ stilius ir 2) primityvi „tautiška“, „kaimiškoji“ stilizacija interjeruose. Kičas siejamas su postmodernizmu, kuris propaguoja eklektizmą, „kaimiškąsias“ formas, stilizaciją, istorizmo tendencijas.Reikšminiai žodžiai: kičas, eklektika, komercinis interjeras, „tautiškasis“, „kaimiškasis“ kičas, postmodernizmas.First Published Online: 22 May 2013